Ornithological importance and phenological status of the avifauna population of the Idriss 1st dam in semi-arid climate Morocco - ISSAOUI, Ayoub EL; AJDI, Mouhcine; BOUHADDIOUI, Abderrahim; BAHHOU, Jamila (Edelweiss Applied Science and Technology, 2025)
This study evaluates the ornithological diversity and phenological status of bird species at Idriss I Dam, located 21 km northeast of Fez, Morocco. From 2022 to 2024, avifaunal monitoring was conducted on a monthly to bimonthly basis, accounting for both seasonal and interannual variations. Observation points were selected based on water-level fluctuations, and bird counts were carried out using 12×50 binoculars and a Nikon P1000 camera. The avifaunal structure was analyzed using ecological indices, including total abundance, species richness, and the Shannon–Wiener diversity index. Seventy-eight waterbird species from 21 families were recorded, with Anatidae (20%) and Scolopacidae (15%) being the most represented, followed by Ardeidae (11%) and Laridae (9%). Diversity indices indicated high species richness, with Shannon index values ranging from 2.83 to 3.02 bits per individual, confirming the site’s importance as a wintering, resting, and breeding habitat. Seven dominant species were identified: black-headed gull, mallard, green-winged teal, common crane, great cormorant, northern shoveler, and ruddy shelduck. Occasional records of endangered or vulnerable species, such as the Egyptian vulture and common pochard, were also documented. Principal Component Analysis revealed three main phenological phases: post-nuptial migration, wintering, and pre-nuptial migration, underscoring the site’s ecological significance and supporting its potential designation as a Ramsar site.